Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4187/respcare.00986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Family Caregiver Caring Behavior on COPD Patients' Self-Care Behavior in Taiwan

Abstract: Family caregivers' caring behavior had a partial negative effect on COPD patients' self-care behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Previous studies [20][21][22] reported that people with disabilities, including poststroke patients, in China and Taiwan had diminished expectations of their independence. Wang et al 22 explained that family members tend to provide too much assistance in self-care activities performed by the patients. After the onset of stroke, as primary caregivers, family members tended to overprotect poststroke patients by assisting them in their BADL tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies [20][21][22] reported that people with disabilities, including poststroke patients, in China and Taiwan had diminished expectations of their independence. Wang et al 22 explained that family members tend to provide too much assistance in self-care activities performed by the patients. After the onset of stroke, as primary caregivers, family members tended to overprotect poststroke patients by assisting them in their BADL tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Other domains, assessed in the studies, comprised both the negative and positive aspects of caregiving (Caregiver Reaction Assessment [25,47,61,62]; Family Appraisal of Caregiving Questionnaire for Palliative Care [23,63]), disability due to the partner's disease (COPD Disability Index [50], which was a modified version of the Pain Disability Index), objective and subjective health status (Health Perceptions Questionnaire Form II e only the Current Health subscale was used [48]), low back pain prevalence and impact (Nordic low back pain questionnaire [60]), psychosocial impact of the illness (Psychosocial Adjustment to Illness Scale e Self-Report [32,33]), loneliness (revised UCLA Loneliness scale [43,64]), spiritual wellbeing (Functional Assessment of Chronic Illness Therapy 12-item Spiritual Well-Being Scale [47]) and life satisfaction (Life Satisfaction Index-A [65]).…”
Section: Instrumentsmentioning
confidence: 99%
“…Informal caregiving may also have negative consequences. Patients' self-care behaviour may decrease with higher levels of caring behaviour from informal caregivers [15]. Informal caregivers can be overprotective [16], and COPD patients living together with an informal caregiver may be more dependent in instrumental activities of daily living [14].…”
Section: Role Of Informal Caregiversmentioning
confidence: 99%